2019
DOI: 10.2131/jts.44.415
|View full text |Cite
|
Sign up to set email alerts
|

Polyhexamethylene guanidine phosphate-induced ROS-mediated DNA damage caused cell cycle arrest and apoptosis in lung epithelial cells

Abstract: Polyhexamethylene guanidine phosphate (PHMG-p) is an active ingredient of humidifier disinfectants and causes severe lung injury resulting in pulmonary fibrosis. Current evidence indicates that pulmonary fibrosis is initiated as a result of epithelial damage, which can lead to an inflammatory response and fibrotic cell infiltration; however, the toxic mechanism of PHMG-p on the epithelium is still unknown. In this study, the toxic response of PHMG-p on human lung epithelial cells was evaluated, and its mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 33 publications
3
17
0
1
Order By: Relevance
“…These results indicated that TRF2 degraded by DHA in Eca109 cells caused DDR. A previous study showed that ROS induced by polyhexamethylene guanidine phosphate caused DDR in lung epithelial cells [39]. In our study, we found that inhibited ROS by NAC could not significantly reduce the expression of γ-H2AX, which indicated that DDR induced by DHA might be partially through ROS, the exact mechanisms should be uncovered further.…”
Section: Discussionmentioning
confidence: 50%
“…These results indicated that TRF2 degraded by DHA in Eca109 cells caused DDR. A previous study showed that ROS induced by polyhexamethylene guanidine phosphate caused DDR in lung epithelial cells [39]. In our study, we found that inhibited ROS by NAC could not significantly reduce the expression of γ-H2AX, which indicated that DDR induced by DHA might be partially through ROS, the exact mechanisms should be uncovered further.…”
Section: Discussionmentioning
confidence: 50%
“…First, ROS directly damages the DNA of target cells. Previous research has shown that ROS produced from activated neutrophils induces oxidative DNA damage in respiratory epithelial cells [ 54 , 55 ]. Moreover, hyperoxia with 95% oxygen induces either neutrophil influx or oxidative DNA damage in neonate lung epithelial cells [ 56 ].…”
Section: Role Of Neutrophils In Ardsmentioning
confidence: 99%
“…Guanidine-based disinfectants, PHMG-P, polyhexamethylene biguanide (PHMB), and oligo (2- (2-ethoxy) ethoxyethyl guanidinium chloride (PGH) induce epithelial-mesenchymal transition in A549 alveolar epithelial cells [ 4 ]. PHMG-P promotes reactive oxygen species (ROS) generation and consequently increases the expression of DNA damage markers, such as ATM and H2AX phosphorylation [ 5 ]. NOTCH1 transcripts significantly increased in lung tissues from HDLI cases compared to unexposed controls (p=0.05), so NOTCH1 may play an important role in the pulmonary fibrosis of HDLI [ 6 ].…”
Section: Introduction: Humidifier Disinfectants (Hds) Study Results Smentioning
confidence: 99%